CRITICAL SUCCESS FACTORS OF AGILE SOFTWARE DEVELOPMENT IN WATERFALL PROJECT: A CASE STUDY APPROACH - Indra Bayu; Teguh Raharjo; Bob Hardian Syahbuddin (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
The evolution of software development methodologies has seen Agile rise in response to the limitations of traditional approaches like Waterfall, characterized by its iterative, collaborative, and adaptable nature. However, integrating Agile within the rigid, structured frameworks of organizations accustomed to Waterfall presents significant challenges. This study addresses how to effectively combine these methodologies to mitigate conflicts and achieve successful project outcomes by identifying and analyzing the Critical Success Factors (CSFs) that enable a harmonious integration of Agile into Waterfall environments. Conducted at PT ABC, a firm balancing formal client interactions and contract creation with internal adoption of Scrum, this research uses the Analytic Hierarchy Process (AHP) to systematically prioritize CSFs through literature review, questionnaire development, data collection, and pairwise comparison analysis. The findings reveal that "Communication and Team Environment" is the most influential factor, with a priority vector weight of 0.178, followed by "Project Management and Strategy," "Leadership and Management Support," and "User and Customer Engagement." These factors are pivotal in achieving a balance between control and flexibility in software development projects. The study's implications for PT ABC and other organizations, especially those handling multiple projects and requiring on-site presence while managing other projects, demonstrate how to leverage the strengths of both methodologies for optimal project outcomes. This research provides a model for other organizations striving for similar integrative efforts, showcasing practical strategies to enhance project flexibility and coordination.